Gold-titanium alloy nanoparticles as well as wet chemical preparation method and application thereof
The preparation of gold-titanium alloy nanoparticles by wet chemistry using a support carrier under high temperature and high pressure conditions has been solved, and the problem of poor agglomeration and dispersion of nanoparticles at high temperatures in the prior art has been achieved, and nanoparticles with efficient catalytic performance has been achieved.
Patent Information
- Application Number
- CN202411760295.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The synthesis of existing gold-titanium alloy nanoparticles at high temperatures can easily lead to agglomeration, increase in particle size and poor dispersion, which limits their application in catalytic reactions.
Wet chemistry method is used to prepare gold-titanium alloy nanoparticles by introducing support under high temperature and high pressure conditions, and the co-reduction principle is used to prevent agglomeration and improve dispersion and catalytic performance.
The prepared gold-titanium alloy nanoparticles have high purity, uniform morphology and excellent catalytic properties, and are suitable for CO thermal oxidation and CO electrochemical oxidation.
Smart Images

Figure CN119566322A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alloy material preparation, and specifically relates to a method for preparing gold-titanium alloy nanoparticles by a wet chemical method, and in particular to a method for preparing gold-titanium alloy nanoparticles by chemically reducing gold salt and titanium salt. The present invention also relates to gold-titanium alloy nanoparticles prepared by the method and their application in catalytic reactions. Background Art
[0002] As a new type of power generation equipment with high working efficiency and environmental protection, hydrogen fuel cells have extremely high requirements for the incoming hydrogen source. Generally, the hydrogen source contains a certain amount of CO, which is easily adsorbed on the surface of the anode catalyst of the battery, seriously affecting the battery performance. In addition, as a toxic and flammable gas, the presence of CO poses a certain hazard to people's life safety. Therefore, the removal of CO has very important economic benefits and social significance. Supported gold nanoparticles can catalyze the CO oxidation reaction at room temperature and are considered to be a good catalyst for the CO oxidation reaction.
[0003] In the CO oxidation reaction, the performance of single metal catalysts is often lower than that of alloy metal catalysts. For gold-based catalysts, the addition of the second phase metal titanium forms a strong synergistic effect with gold, and the charge tends to transfer from titanium to gold, making gold present a negative valence state, increasing the adsorption energy of gold, and is conducive to providing more active oxygen species for the CO oxidation intermediate state, thereby improving the activity of the catalyst. In addition, the alloying of gold and titanium is also conducive to improving the stability and sintering resistance of gold-based materials. Small-particle gold nanoparticles are often synthesized in alkaline aqueous solutions, but titanium salts are easily hydrolyzed when exposed to water, and are also easily reacted with alkaline solutions to form precipitation. In addition, there is an extremely high reduction potential difference between gold and titanium, making it difficult to co-reduce. At present, the methods for preparing gold-titanium alloys are mainly sputtering coating and arc melting, but these methods are complex processes, and the prepared materials have large particles and low specific surface area, which greatly limits their application in the field of catalysis.
[0004] Publication number is that the Chinese patent of CN108927154A discloses a kind of preparation method of intermetallic compound nano catalyst, and this method joins strong reducing agent in bimetallic salt ether solution at normal temperature and pressure, and the reduction product is directly washed or transferred to the washing after high boiling point solvent reflux, and through vacuum drying, obtains intermetallic compound nano catalyst material.But the intermetallic compound nano particle dispersion obtained by above-mentioned patent reduction is poor, and it can be obviously seen that the aggregation and adhesion of particle, in shown naphthalene selective hydrogenation catalytic reaction, because reaction is carried out under high temperature condition, intermetallic compound nano particle will certainly face the problems such as greater degree of reunion, particle diameter growth.And in catalytic reaction, the interaction of metal and carrier plays an important role, and there is no introduction of carrier in this patent preparation process, which seriously limits its application in catalytic reaction. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing gold-titanium alloy nanoparticles by a wet chemical method in order to address the technical problems that the existing alloy nanoparticles will agglomerate when synthesized at high temperature, resulting in increased particle size and poor dispersibility. By utilizing the co-reduction principle, gold-titanium alloy nanoparticles with high purity, uniform morphology and excellent catalytic performance are obtained by introducing a supporting carrier under high temperature and high pressure.
[0006] Another object of the present invention is to provide the use of the above-mentioned gold-titanium alloy nanoparticles as a catalyst in CO thermal oxidation or CO electrochemical oxidation.
[0007] To achieve its purpose, the present invention adopts the following technical solution: A method for preparing gold-titanium alloy nanoparticles by wet chemical method, characterized in that it comprises the following steps: (1) In an anhydrous and oxygen-free environment, gold salt, titanium salt, and a supporting carrier are dissolved in an ether solvent and mixed with lithium triethylborohydride; the molar ratio of the gold salt to the titanium salt is 1:1-8, and the molar ratio of the total amount of the gold salt, the titanium salt, and the lithium triethylborohydride is 1:4-7.
[0008] When the ratio of gold salt to titanium salt is higher than 1:1, the degree of alloying will be affected, and the purpose of improving the catalytic activity of gold-based nanoparticles by gold-titanium alloying cannot be achieved, and the alloy nanoparticles will tend to agglomerate from dispersion; when it is lower than 1:8, a large amount of amorphous titanium oxide will be formed on the alloy surface, covering the catalytic active sites of gold and affecting the catalytic performance; when the ratio of the total amount of gold salt, titanium salt and lithium triethylborohydride is higher than 1:4, gold and titanium reduction will be insufficient, and when it is lower than 1:7, the reducing agent lithium triethylborohydride will be wasted.
[0009] (2) After the solution in step (1) is mixed uniformly, the mixed solution is placed in a high pressure reactor, and heated to 180-220°C under an inert gas pressure of 0.5-1 MPa with stirring, and kept warm for 1-4 hours.
[0010] A pressure lower than 0.5 MPa or a temperature lower than 180°C will reduce the interaction between the metal and the carrier, affecting its anti-sintering performance and catalytic performance; a pressure higher than 1 MPa or a temperature higher than 220°C will cause the size of the alloy nanoparticles to increase, the range of particle size variation to increase, and the shape to become non-uniform.
[0011] (3) After the reaction in step (2) is completed, the mixture is cooled to room temperature, the product solution is diluted with n-hexane, and centrifuged at a speed of 9000-12000 r / min. The precipitate is washed and vacuum dried to obtain gold-titanium alloy nanoparticles.
[0012] As a further preferred embodiment of the technical solution of the present invention, in step (1), the gold salt is selected from one or more of gold chloride, gold bromide, gold iodide, sodium gold chloride or potassium gold chloride.
[0013] Lithium triethylborohydride, as a strong nucleophilic hydrogen source, is suitable for the reduction reaction of halides, so gold halide is selected as the gold source.
[0014] Furthermore, in step (1), the titanium salt is selected from one or more of titanium chloride, titanium bromide, titanium iodide or titanium fluoride.
[0015] Lithium triethylborohydride, as a strong nucleophilic hydrogen source, is suitable for the reduction reaction of halides, so titanium halide is selected as the titanium source.
[0016] Furthermore, in step (1), the support carrier is selected from one or more of carbon, titanium dioxide, cerium dioxide or SBA-15, or one or more of sodium chloride, potassium chloride and calcium oxide.
[0017] Carbon, titanium dioxide, cerium dioxide or SBA-15 are commonly used catalyst supports in CO thermal oxidation or CO electrochemical oxidation; sodium chloride, potassium chloride and calcium oxide are insoluble in ether solvents and are easy to remove. After removal, dispersed carrier-free gold-titanium alloy nanoparticles can be obtained, which is conducive to further exploring the performance of gold-titanium alloy nanoparticles.
[0018] Furthermore, when the supporting carrier is selected from one or more of carbon, titanium dioxide, cerium dioxide or SBA-15, the mixing ratio of the supporting carrier to the total amount of gold salt and titanium salt is 10~50 mg:0.1 mmol; when the supporting carrier is selected from one or more of sodium chloride, potassium chloride or calcium carbonate, the mixing ratio of the supporting carrier to the total amount of gold salt and titanium salt is 100~500 mg:0.1 mmol.
[0019] Too little support carrier will cause particle agglomeration, while too much support carrier will lead to reduced alloying degree of gold-titanium alloy nanoparticles, too little loading amount, reduced catalytic activity, and waste of support carrier.
[0020] Furthermore, in step (1), the mixing ratio of the total amount of the gold salt, the titanium salt and the ether solvent is 0.1 mmol:7.5 ~ 15 mL.
[0021] Furthermore, the ether solvent is selected from one or more of diethylene glycol dimethyl ether, ethylene glycol dimethyl ether or tetrahydrofuran.
[0022] Diethylene glycol dimethyl ether, ethylene glycol dimethyl ether or tetrahydrofuran is one of the common ether solvents with low boiling point and volatility, and is widely used in the synthesis and preparation of products.
[0023] Furthermore, in step (3), the cleaning reagent is selected from one or more of n-hexane, acetonitrile, toluene, tetrahydrofuran or anhydrous ethanol.
[0024] The gold-titanium alloy nanoparticles prepared by the wet chemical preparation method have high purity, uniform morphology, and excellent catalytic performance, and can be used as a catalyst in CO thermal oxidation or CO electrochemical oxidation.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses a wet chemical method to reduce the gold salt and titanium salt adsorbed on the support carrier using a strong reducing agent, lithium triethylborohydride, under high temperature and high pressure conditions to prepare highly dispersed nanoparticles with uniform particle size, providing a simple method for preparing gold-titanium alloy nanoparticles. The introduction of the support carrier avoids the problem of increasing the particle size caused by the agglomeration of gold-titanium alloy nanoparticles at high temperatures, improves the degree of dispersion, and the size of the prepared gold-titanium alloy nanoparticles is between 4-10nm. The gold-titanium alloy nanoparticles and the carrier will have a strong interaction, which enhances their catalytic performance and anti-sintering performance, and has broad application prospects in the fields of CO thermal oxidation and CO electrochemical oxidation; (2) The gold-titanium alloy nanoparticles of the present invention are prepared in a short time and do not introduce new impurities, and the obtained product is pure; (3) In the preparation process of gold-titanium alloy nanoparticles, easily removable carriers such as sodium chloride and potassium chloride are used. After washing and removing, unloaded and uniform nanoparticles can be obtained; (4) The preparation method of the present invention is simple, low-cost and can be prepared on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The X-ray diffraction pattern of the titanium dioxide-loaded gold-titanium alloy nanoparticles prepared in Example 1 of the present invention; Figure 2 This is a transmission electron micrograph of titanium dioxide-loaded gold-titanium alloy nanoparticles prepared in Example 1 of the present invention; Figure 3 This is an X-ray diffraction pattern of carbon-supported gold-titanium alloy nanoparticles prepared in Example 2 of the present invention; Figure 4 This is a transmission electron micrograph of carbon-supported gold-titanium alloy nanoparticles prepared in Example 2 of the present invention; Figure 5 This is an X-ray diffraction pattern of SBA-15 loaded with gold-titanium alloy nanoparticles prepared in Example 3 of the present invention; Figure 6 This is a transmission electron micrograph of SBA-15 loaded with gold-titanium alloy nanoparticles prepared in Example 3 of the present invention; Figure 7 This is an X-ray diffraction pattern of the sodium chloride-loaded gold-titanium alloy nanoparticles prepared in Example 4 of the present invention after washing to remove the sodium chloride; Figure 8 This is a transmission electron micrograph of sodium chloride-loaded gold-titanium alloy nanoparticles prepared in Example 4 of the present invention; Fig. 9 The grayscale image and EDS image of the sodium chloride-loaded gold-titanium alloy nanoparticles prepared in Example 4 of the present invention under a transmission electron microscope; Fig.10 This is a transmission electron micrograph of titanium dioxide-loaded gold-titanium alloy nanoparticles prepared in Example 5 of the present invention; Fig.11 This is a transmission electron micrograph of calcium oxide-loaded gold-titanium alloy nanoparticles prepared in Example 6 of the present invention; Fig.12 This is a transmission electron micrograph of carbon-supported gold-titanium alloy nanoparticles prepared in Example 7 of the present invention; Fig.13 This is a transmission electron micrograph of carbon-supported gold-titanium alloy nanoparticles prepared in Example 8 of the present invention; Fig.14 This is a transmission electron micrograph of sodium chloride-loaded gold-titanium alloy nanoparticles prepared in Example 9 of the present invention. DETAILED DESCRIPTION
[0027] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0028] Example 1 A method for preparing gold-titanium alloy nanoparticles by wet chemical method, the specific process of the method comprises the following steps: (1) In an anhydrous and oxygen-free environment, a certain proportion of gold salt, titanium salt, and titanium dioxide are dissolved in an ether solvent and mixed with a certain amount of lithium triethylborohydride. The specific steps are as follows: (a) Add 0.1 mmol gold bromide, 0.1 mmol titanium bromide and 60 mg titanium dioxide to 30 mL of diethylene glycol dimethyl ether solvent and stir evenly; (b) Take 1 mL of 1 mol / L lithium triethylborohydride solution, slowly add it to the mixed solution (a), and stir evenly to obtain a mixed solution.
[0029] (2) The mixed solution in step (1) is subjected to a pressure reaction, and the specific steps are as follows: (a) The mixed solution was placed in a high pressure reactor, heated to 200 °C at a speed of 500 r / min under an argon pressure of 0.5 MPa, and kept at this temperature for 2 hours; (b) After the solution in (a) is cooled to room temperature, a gold-titanium nanoalloy organic solution is obtained and transferred into a high-speed centrifuge tube.
[0030] (3) Washing and drying the product obtained in step (2), the specific steps are as follows: (a) adding n-hexane to a high-speed centrifuge tube to dilute the gold-titanium nanoalloy organic solution and wash it, centrifuging it at 10,000 r / min for 5 min until the supernatant becomes transparent, and taking the precipitate; (b) Add 30 mL of acetonitrile to the precipitate, centrifuge at 10,000 r / min for 5 min, and take out the precipitate; (c) The final precipitate was vacuum dried for 1 hour to obtain titanium dioxide-supported gold-titanium nanoalloy particles, whose X-ray diffraction pattern is shown in FIG. Figure 1 As shown in the transmission electron microscopy image Figure 2 shown.
[0031] Figure 1 The results showed that compared with the characteristic peak of the PDF standard card PDF#98-000-2320 of pure gold, the characteristic peak position of the gold-titanium alloy nanoparticles prepared in this example shifted toward the high angle direction, indicating that titanium atoms were incorporated into the face-centered cubic lattice of gold to generate an alloy phase. Figure 2 The results showed that the gold-titanium alloy nanoparticles prepared in this example had no aggregation or adhesion, were well dispersed on the titanium dioxide carrier, had a uniform shape, and had an average particle size of 7.2 nm.
[0032] Example 2 A method for preparing gold-titanium alloy nanoparticles by wet chemical method, the specific process of the method comprises the following steps: (1) In an anhydrous and oxygen-free environment, a certain proportion of gold salt, titanium salt, and titanium dioxide are dissolved in an ether solvent and mixed with a certain amount of lithium triethylborohydride. The specific steps are as follows: (a) Add 0.1 mmol gold bromide, 0.1 mmol titanium bromide and 60 mg carbon to 30 mL of diethylene glycol dimethyl ether solvent and stir evenly; (b) Take 1 mL of 1 mol / L lithium triethylborohydride solution, slowly add it to the mixed solution (a), and stir evenly to obtain a mixed solution.
[0033] (2) The mixed solution in step (1) is subjected to a pressure reaction, and the specific steps are as follows: (a) The mixed solution was placed in a high pressure reactor, heated to 200 °C at a speed of 500 r / min under an argon pressure of 0.5 MPa, and kept at this temperature for 2 hours; (b) After the solution in (a) is cooled to room temperature, a gold-titanium nanoalloy organic solution is obtained and transferred into a high-speed centrifuge tube.
[0034] (3) Washing and drying the product obtained in step (2), the specific steps are as follows: (a) adding n-hexane to a high-speed centrifuge tube to dilute the gold-titanium nanoalloy organic solution and wash it, centrifuging it at 10,000 r / min for 5 min until the supernatant becomes transparent, and taking the precipitate; (b) Add 30 mL of acetonitrile to the precipitate, centrifuge at 10,000 r / min for 5 min, and take out the precipitate; (c) The final precipitate was vacuum dried for 1 hour to obtain carbon-supported gold-titanium nanoalloy particles, whose X-ray diffraction pattern is shown in FIG. Figure 3 As shown in the transmission electron microscopy image Figure 4 shown.
[0035] Figure 3 The results showed that compared with the characteristic peak of the PDF standard card PDF#98-000-2320 of pure gold, the characteristic peak position of the gold-titanium alloy nanoparticles prepared in this example shifted toward the high angle direction, indicating that titanium atoms were incorporated into the face-centered cubic lattice of gold to generate an alloy phase. Figure 4 The results show that the gold-titanium alloy nanoparticles prepared in this example have no aggregation or adhesion phenomenon, are excellently dispersed on the carbon carrier, have a uniform shape, and have an average particle size of 4.9 nm.
[0036] Example 3 A method for preparing gold-titanium alloy nanoparticles by wet chemical method, the specific process of the method comprises the following steps: (1) In an anhydrous and oxygen-free environment, a certain proportion of gold salt, titanium salt, and SBA-15 are dissolved in an ether solvent and mixed with a certain amount of lithium triethylborohydride. The specific steps are as follows: (a) Add 0.1 mmol gold bromide, 0.1 mmol titanium bromide, and 60 mg SBA-15 to 30 mL of tetrahydrofuran solvent and stir evenly; (b) Take 1 mL of 1 mol / L lithium triethylborohydride solution, slowly add it to the mixed solution (a), and stir evenly to obtain a mixed solution.
[0037] (2) The mixed solution in step (1) is subjected to a pressure reaction, and the specific steps are as follows: (a) The mixed solution was placed in a high pressure reactor, heated to 200 °C at a speed of 500 r / min under an argon pressure of 0.5 MPa, and kept at this temperature for 2 hours; (b) After the solution in (a) is cooled to room temperature, a gold-titanium nanoalloy organic solution is obtained and transferred into a high-speed centrifuge tube.
[0038] (3) Washing and drying the product obtained in step (2), the specific steps are as follows: (a) adding n-hexane to a high-speed centrifuge tube to dilute the gold-titanium nanoalloy organic solution and wash it, centrifuging it at 10,000 r / min for 5 min until the supernatant becomes transparent, and taking the precipitate; (b) Add 30 mL of acetonitrile to the precipitate, centrifuge at 10,000 r / min for 5 min, and take out the precipitate; (c) The final precipitate was vacuum dried for 1 hour to obtain SBA-15 loaded gold-titanium nanoalloy particles, whose X-ray diffraction pattern is shown in Figure 5 As shown in the transmission electron microscopy image Figure 6 shown.
[0039] Figure 5 The results showed that compared with the characteristic peak of the PDF standard card PDF#98-000-2320 of pure gold, the characteristic peak position of the gold-titanium alloy nanoparticles prepared in this example shifted toward the high angle direction, indicating that titanium atoms were incorporated into the face-centered cubic lattice of gold to generate an alloy phase. Figure 6 The results show that the gold-titanium alloy nanoparticles prepared in this example have no aggregation or adhesion phenomenon, are excellently dispersed on the SBA-15 carrier, have a uniform shape, and have an average particle size of 3.8 nm.
[0040] Example 4 A method for preparing gold-titanium alloy nanoparticles by wet chemical method, the specific process of the method comprises the following steps: (1) In an anhydrous and oxygen-free environment, a certain proportion of gold salt, titanium salt, and sodium chloride are dissolved in an ether solvent and mixed with a certain amount of lithium triethylborohydride. The specific steps are as follows: (a) Add 0.1 mmol potassium gold chlorate, 0.1 mmol titanium chloride, and 200 mg sodium chloride to 30 mL of tetrahydrofuran solvent and stir evenly; (b) Take 1 mL of 1 mol / L lithium triethylborohydride solution, slowly add it to the mixed solution (a), and stir evenly to obtain a mixed solution.
[0041] (2) The mixed solution in step (1) is subjected to a pressure reaction, and the specific steps are as follows: (a) The mixed solution was placed in a high pressure reactor, heated to 200 °C at a speed of 500 r / min under an argon pressure of 0.5 MPa, and kept at this temperature for 2 hours; (b) After the solution in (a) is cooled to room temperature, a gold-titanium nanoalloy organic solution is obtained and transferred into a high-speed centrifuge tube.
[0042] (3) Washing and drying the product obtained in step (2), the specific steps are as follows: (a) adding n-hexane to a high-speed centrifuge tube to dilute the gold-titanium nanoalloy organic solution and wash it, centrifuging it at 10,000 r / min for 5 min until the supernatant becomes transparent, and taking the precipitate; (b) Add 30 mL of acetonitrile to the precipitate, centrifuge at 10,000 r / min for 5 min, and take out the precipitate; (c) The final precipitate was vacuum dried for 1 hour to obtain gold-titanium nanoalloy particles loaded with sodium chloride, whose X-ray diffraction pattern (washing with water to remove sodium chloride) is as follows: Figure 7 As shown in the transmission electron microscopy image Figure 8 As shown, the grayscale image and EDS image under transmission electron microscope are as follows Fig. 9 shown.
[0043] Figure 7 The results showed that compared with the characteristic peak of the PDF standard card PDF#98-000-2320 of pure gold, the characteristic peak position of the gold-titanium alloy nanoparticles prepared in this example shifted toward the high angle direction, indicating that titanium atoms were incorporated into the face-centered cubic lattice of gold to generate an alloy phase. Figure 8 The results show that the gold-titanium alloy nanoparticles prepared in this example have no aggregation or adhesion, are excellently dispersed on the sodium chloride carrier, have a uniform shape, and have an average particle size of 6.7 nm. Fig. 9 The results showed that the gold and titanium elements in the gold-titanium alloy nanoparticles were evenly dispersed on the sodium chloride carrier.
[0044] Example 5 A method for preparing gold-titanium alloy nanoparticles by wet chemical method, the specific process of the method comprises the following steps: (1) In an anhydrous and oxygen-free environment, a certain proportion of gold salt, titanium salt, and titanium dioxide are dissolved in an ether solvent and mixed with a certain amount of lithium triethylborohydride. The specific steps are as follows: (a) Add 0.1 mmol of potassium gold chloride, 0.8 mmol of titanium chloride, and 270 mg of titanium dioxide to 30 mL of diethylene glycol dimethyl ether solvent and stir evenly; (b) Take 4.5 mL of 1 mol / L lithium triethylborohydride solution, slowly add it to the mixed solution (a), and stir evenly to obtain a mixed solution.
[0045] (2) The mixed solution in step (1) is subjected to a pressure reaction, and the specific steps are as follows: (a) The mixed solution was placed in a high pressure reactor, heated to 200 °C at a speed of 500 r / min under an argon pressure of 0.5 MPa, and kept at this temperature for 2 hours; (b) After the solution in (a) is cooled to room temperature, a gold-titanium nanoalloy organic solution is obtained and transferred into a high-speed centrifuge tube.
[0046] (3) Washing and drying the product obtained in step (2), the specific steps are as follows: (a) adding n-hexane to a high-speed centrifuge tube to dilute the gold-titanium nanoalloy organic solution and wash it, centrifuging it at 10,000 r / min for 5 min until the supernatant becomes transparent, and taking the precipitate; (b) Add 30 mL of acetonitrile to the precipitate, centrifuge at 10,000 r / min for 5 min, and take out the precipitate; (c) The final precipitate was vacuum dried for 1 hour to obtain titanium dioxide-supported gold-titanium nanoalloy particles, the transmission electron microscopy image of which is shown in FIG. Fig.10 shown.
[0047] Fig.10 The results show that the gold-titanium alloy nanoparticles prepared in this example have no aggregation or adhesion phenomenon, are well dispersed on the titanium dioxide carrier, have a uniform shape, and have an average particle size of 4.6 nm.
[0048] Example 6 A method for preparing gold-titanium alloy nanoparticles by wet chemical method, the specific process of the method comprises the following steps: (1) In an anhydrous and oxygen-free environment, a certain proportion of gold salt, titanium salt, and calcium oxide are dissolved in an ether solvent and mixed with a certain amount of lithium triethylborohydride. The specific steps are as follows: (a) Add 0.1 mmol gold bromide, 0.1 mmol titanium bromide and 60 mg calcium oxide to 30 mL of diethylene glycol dimethyl ether solvent and stir evenly; (b) Take 1 mL of 1 mol / L lithium triethylborohydride solution, slowly add it to the mixed solution (a), and stir evenly to obtain a mixed solution.
[0049] (2) The mixed solution in step (1) is subjected to a pressure reaction, and the specific steps are as follows: (a) The mixed solution was placed in a high pressure reactor, heated to 200 °C at a speed of 500 r / min under an argon pressure of 0.5 MPa, and kept at this temperature for 2 hours; (b) After the solution in (a) is cooled to room temperature, a gold-titanium nanoalloy organic solution is obtained and transferred into a high-speed centrifuge tube.
[0050] (3) Washing and drying the product obtained in step (2), the specific steps are as follows: (a) adding n-hexane to a high-speed centrifuge tube to dilute the gold-titanium nanoalloy organic solution and wash it, centrifuging it at 10,000 r / min for 5 min until the supernatant becomes transparent, and taking the precipitate; (b) Add 30 mL of acetonitrile to the precipitate, centrifuge at 10,000 r / min for 5 min, and take out the precipitate; (c) The final precipitate was vacuum dried for 1 hour to obtain calcium oxide-supported gold-titanium nanoalloy particles, the transmission electron microscopy image of which is shown in FIG. Fig.11 shown.
[0051] Fig.11 The results show that the gold-titanium alloy nanoparticles prepared in this example have no aggregation or adhesion phenomenon, are well dispersed on the calcium oxide carrier, have a uniform shape, and have an average particle size of 8.4 nm.
[0052] Example 7 A method for preparing gold-titanium alloy nanoparticles by wet chemical method, the specific process of the method comprises the following steps: (1) In an anhydrous and oxygen-free environment, a certain proportion of gold salt, titanium salt, and carbon are dissolved in an ether solvent and mixed with a certain amount of lithium triethylborohydride. The specific steps are as follows: (a) Add 0.1 mmol gold bromide, 0.1 mmol titanium bromide and 20 mg carbon to 30 mL of diethylene glycol dimethyl ether solvent and stir evenly; (b) Take 1 mL of 1 mol / L lithium triethylborohydride solution, slowly add it to the mixed solution (a), and stir evenly to obtain a mixed solution.
[0053] (2) The mixed solution in step (1) is subjected to a pressure reaction, and the specific steps are as follows: (a) The mixed solution was placed in a high pressure reactor, heated to 180 °C at a speed of 500 r / min under an argon pressure of 0.5 MPa, and kept at this temperature for 2 hours; (b) After the solution in (a) is cooled to room temperature, a gold-titanium nanoalloy organic solution is obtained and transferred into a high-speed centrifuge tube.
[0054] (3) Washing and drying the product obtained in step (2), the specific steps are as follows: (a) adding n-hexane to a high-speed centrifuge tube to dilute the gold-titanium nanoalloy organic solution and wash it, centrifuging it at 10,000 r / min for 5 min until the supernatant becomes transparent, and taking the precipitate; (b) Add 30 mL of acetonitrile to the precipitate, centrifuge at 10,000 r / min for 5 min, and take out the precipitate; (c) The final precipitate was vacuum dried for 1 hour to obtain carbon-supported gold-titanium nanoalloy particles, the transmission electron microscopy image of which is shown in FIG. Fig.12 shown.
[0055] Fig.12 The results show that the gold-titanium alloy nanoparticles prepared in this example have no aggregation or adhesion phenomenon, are excellently dispersed on the carbon carrier, have a uniform shape, a high density, and an average particle size of 5.1 nm.
[0056] Example 8 A method for preparing gold-titanium alloy nanoparticles by wet chemical method, the specific process of the method comprises the following steps: (1) In an anhydrous and oxygen-free environment, a certain proportion of gold salt, titanium salt, and carbon are dissolved in an ether solvent and mixed with a certain amount of lithium triethylborohydride. The specific steps are as follows: (a) Add 0.1 mmol gold bromide, 0.1 mmol titanium bromide and 100 mg carbon to 30 mL of diethylene glycol dimethyl ether solvent and stir evenly; (b) Take 1 mL of 1 mol / L lithium triethylborohydride solution, slowly add it to the mixed solution (a), and stir evenly to obtain a mixed solution.
[0057] (2) The mixed solution in step (1) is subjected to a pressure reaction, and the specific steps are as follows: (a) The mixed solution was placed in a high pressure reactor, heated to 220 °C at a speed of 500 r / min under an argon pressure of 0.5 MPa, and kept at this temperature for 2 hours; (b) After the solution in (a) is cooled to room temperature, a gold-titanium nanoalloy organic solution is obtained and transferred into a high-speed centrifuge tube.
[0058] (3) Washing and drying the product obtained in step (2), the specific steps are as follows: (a) adding n-hexane to a high-speed centrifuge tube to dilute the gold-titanium nanoalloy organic solution and wash it, centrifuging it at 10,000 r / min for 5 min until the supernatant becomes transparent, and taking the precipitate; (b) Add 30 mL of acetonitrile to the precipitate, centrifuge at 10,000 r / min for 5 min, and take out the precipitate; (c) The final precipitate was vacuum dried for 1 hour to obtain carbon-supported gold-titanium nanoalloy particles, the transmission electron microscopy image of which is shown in FIG. Fig.13 shown.
[0059] Fig.13The results show that the gold-titanium alloy nanoparticles prepared in this example have no aggregation or adhesion, are excellently dispersed on the carbon carrier, have a uniform shape, a low density, and an average particle size of 4.7 nm.
[0060] Example 9 A method for preparing gold-titanium alloy nanoparticles by wet chemical method, the specific process of the method comprises the following steps: (1) In an anhydrous and oxygen-free environment, a certain proportion of gold salt, titanium salt, and sodium chloride are dissolved in an ether solvent and mixed with a certain amount of lithium triethylborohydride. The specific steps are as follows: (a) Add 0.1 mmol of potassium gold chlorate, 0.1 mmol of titanium chloride and 1 g of sodium chloride to 30 mL of diethylene glycol dimethyl ether solvent and stir evenly; (b) Take 1 mL of 1 mol / L lithium triethylborohydride solution, slowly add it to the mixed solution (a), and stir evenly to obtain a mixed solution.
[0061] (2) The mixed solution in step (1) is subjected to a pressure reaction, and the specific steps are as follows: (a) The mixed solution was placed in a high pressure reactor, heated to 220 °C at a speed of 500 r / min under an argon pressure of 0.5 MPa, and kept at this temperature for 2 hours; (b) After the solution in (a) is cooled to room temperature, a gold-titanium nanoalloy organic solution is obtained and transferred into a high-speed centrifuge tube.
[0062] (3) Washing and drying the product obtained in step (2), the specific steps are as follows: (a) adding n-hexane to a high-speed centrifuge tube to dilute the gold-titanium nanoalloy organic solution and wash it, centrifuging it at 10,000 r / min for 5 min until the supernatant becomes transparent, and taking the precipitate; (b) Add 30 mL of acetonitrile to the precipitate, centrifuge at 10,000 r / min for 5 min, and take out the precipitate; (c) The final precipitate was vacuum dried for 1 hour to obtain carbon-supported gold-titanium nanoalloy particles, the transmission electron microscopy image of which is shown in FIG. Fig.14 shown.
[0063] Fig.14 The results showed that the gold-titanium alloy nanoparticles prepared in this example had no aggregation or adhesion, were well dispersed on the sodium chloride carrier, had a uniform shape, and had an average particle size of 8.3 nm.
Claims
1. A method for preparing gold-titanium alloy nanoparticles by wet chemical method, characterized in that: The following steps are involved: (1) dissolving a gold salt, a titanium salt, and a support carrier in an ether solvent under an anhydrous and oxygen-free environment, and mixing the mixture with lithium triethylborohydride; the molar ratio of the gold salt to the titanium salt is 1:1-8, and the molar ratio of the total amount of the gold salt, the titanium salt, and the lithium triethylborohydride is 1:4-7; (2) After the solution in step (1) is mixed evenly, the mixed solution is placed in a high pressure reactor, stirred and heated to 180-220°C under an inert gas pressure of 0.5-1 MPa, and kept warm for 1-4 hours; (3) After the reaction in step (2) is completed, the mixture is cooled to room temperature, the product solution is diluted with n-hexane, and centrifuged at a speed of 9000-12000 r / min. The precipitate is washed and vacuum dried to obtain gold-titanium alloy nanoparticles.
2. The method for preparing gold-titanium alloy nanoparticles by wet chemical method according to claim 1, characterized in that: In step (1), the gold salt is selected from one or more of gold chloride, gold bromide, gold iodide, sodium gold chloride or potassium gold chloride.
3. The method for preparing gold-titanium alloy nanoparticles by wet chemical method according to claim 2, characterized in that: In step (1), the titanium salt is selected from one or more of titanium chloride, titanium bromide, titanium iodide or titanium fluoride.
4. The method for preparing gold-titanium alloy nanoparticles by wet chemical method according to claim 3, characterized in that: In step (1), the support carrier is selected from one or more of carbon, titanium dioxide, cerium dioxide or SBA-15, or one or more of sodium chloride, potassium chloride or calcium oxide.
5. The method for preparing gold-titanium alloy nanoparticles by wet chemical method according to claim 4, characterized in that: When the support carrier is selected from one or more of carbon, titanium dioxide, cerium dioxide or SBA-15, the mixing ratio of the support carrier to the total amount of gold salt and titanium salt is 10~50 mg:0.1 mmol; when the support carrier is selected from one or more of sodium chloride, potassium chloride or calcium oxide, the mixing ratio of the support carrier to the total amount of gold salt and titanium salt is 100~500 mg:0.1 mmol.
6. The method for preparing gold-titanium alloy nanoparticles by wet chemical method according to claim 1, characterized in that: In step (1), the mixing ratio of the total amount of the gold salt, the titanium salt and the ether solvent is 0.1 mmol:7.5 ~ 15 mL.
7. The method for preparing gold-titanium alloy nanoparticles by wet chemical method according to claim 6, characterized in that: The ether solvent is selected from one or more of diethylene glycol dimethyl ether, ethylene glycol dimethyl ether or tetrahydrofuran.
8. The method for preparing gold-titanium alloy nanoparticles by wet chemical method according to claim 1, characterized in that: In step (3), the cleaning reagent is selected from one or more of n-hexane, acetonitrile, toluene, tetrahydrofuran or anhydrous ethanol.
9. Gold-titanium alloy nanoparticles prepared by the wet chemical preparation method according to any one of claims 1 to 8.
10. Use of the gold-titanium alloy nanoparticles as claimed in claim 9 as a catalyst in CO thermal oxidation or CO electrochemical oxidation.
Citation Information
Patent Citations
Preparation method of intermetallic compound nano catalyst
CN108927154A
Cited By
Method for preparing homogeneous copper-tantalum nano alloy powder through wet chemical method
CN117532007A
Solvothermal preparation process of rare earth hydride nanoparticles
CN121553902A
A solvothermal process for the preparation of rare earth hydride nanoparticles
CN121553902B